2019
DOI: 10.1111/mpp.12807
|View full text |Cite|
|
Sign up to set email alerts
|

Xanthomonas oryzae pv. oryzae XopQ protein suppresses rice immune responses through interaction with two 14‐3‐3 proteins but its phospho‐null mutant induces rice immune responses and interacts with another 14‐3‐3 protein

Abstract: SummaryMany bacterial phytopathogens employ effectors secreted through the type‐III secretion system to suppress plant innate immune responses. The Xanthomonas type‐III secreted non‐TAL effector protein Xanthomonas outer protein Q (XopQ) exhibits homology to nucleoside hydrolases. Previous work indicated that mutations which affect the biochemical activity of XopQ fail to affect its ability to suppress rice innate immune responses, suggesting that the effector might be acting through some other pathway or mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…In order to check if XopX would interact with any of the rice 14-3-3 proteins, we cloned the wild-type xopX gene in the pDEST32 vector yielding the BD∷xopX (DNA-Binding Domain) clone (as listed in Supplementary table S2). We screened xopX against the eight rice 14-3-3 proteins cloned in the pDEST22 vector yielding the AD∷gf14a-h (Activation Domain) clones used in an earlier study (Deb et al, 2019) (listed in Supplementary table S2), using the yeast two-hybrid system and the yeast strain pJ694a (James et al, 1996). The one-to-one yeast two-hybrid screen indicated that the XopX protein showed physical interaction with two of the eight rice 14-3-3 proteins, Gf14d and Gf14e (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to check if XopX would interact with any of the rice 14-3-3 proteins, we cloned the wild-type xopX gene in the pDEST32 vector yielding the BD∷xopX (DNA-Binding Domain) clone (as listed in Supplementary table S2). We screened xopX against the eight rice 14-3-3 proteins cloned in the pDEST22 vector yielding the AD∷gf14a-h (Activation Domain) clones used in an earlier study (Deb et al, 2019) (listed in Supplementary table S2), using the yeast two-hybrid system and the yeast strain pJ694a (James et al, 1996). The one-to-one yeast two-hybrid screen indicated that the XopX protein showed physical interaction with two of the eight rice 14-3-3 proteins, Gf14d and Gf14e (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The wild-type copy of the xopX gene and its 14-3-3 protein binding motif mutants were cloned in the yeast two-hybrid vector pDEST32 (Invitrogen) using the Gateway cloning system (Invitrogen, California). The eight rice 14-3-3 genes cloned in the yeast two-hybrid vector pDEST22 (Invitrogen) were used from a previous study (Deb et al, 2019). For analysis of interaction of xopX with the other effector proteins, the pDEST22 clones containing xopN , xopQ and xopZ were used, whereas xopX was cloned in pDEST32.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations